The Role of Artificial Intelligence in Increasing Efficiency and Productivity in the World of Work - Dwi Puspita Anggraeni (Technologia Journal, 2025)
The development of artificial intelligence (AI) has brought significant changes to the world of work, particularly in terms of efficiency and productivity. This study aims to analyze the role of AI in supporting operational efficiency, increasing employee productivity, and identifying challenges and opportunities arising from its implementation. The research method used was qualitative with a descriptive approach, where data was collected through in-depth interviews, observations, and documentation in organizations that have implemented AI. Data analysis was conducted using thematic analysis techniques to identify patterns, themes, and implications of AI use. The results show that AI can improve work efficiency by automating routine tasks, reducing human error, and accelerating the decision-making process. Furthermore, labor productivity increases because workers can focus more on strategic and value-added activities. However, challenges were also identified in the form of workforce resistance due to concerns about job losses and the need to improve digital skills. This study concludes that AI impacts not only technical aspects but also social and managerial dimensions, thus requiring a balanced integration strategy between technology and human resource development.